Dwa typy stowarzyszeń społecznych w publikacjach tygodnika „Polityka” - Furman, Wojciech (Polityka i Społeczeństwo, 2020)
The purpose of this article was to examine if both types of social associations, as proposed by Michael Oakeshott, had been present in the chosen publications of Polityka weekly magazine. First the main characteristics of journalist messages were described. An important part of these characteristics applies to relations between journalists and politicians and between journalists and the idea of common good. On this basis four different concepts of journalism were distinguished. The analysis revealed that both types of associations could be identified in the journalists’ messages, and that the differences between these associations were significant.